HCMV Induces Macropinocytosis for Host Cell Entry in Fibroblasts. (11th February 2016) - Hetzenecker, Stefanie; Helenius, Ari; Krzyzaniak, Magdalena Anna
Abstract : Human cytomegalovirus (HCMV) is an important and widespread pathogen in the human population. While infection by this β‐herpesvirus in endothelial, epithelial and dendritic cells depends on endocytosis, its entry into fibroblasts is thought to occur by direct fusion of the viral envelope with the plasma membrane. To characterize individual steps during entry in primary human fibroblasts, we employed quantitative assays as well as electron, fluorescence and live cell microscopy in combination with a variety of inhibitory compounds. Our results showed that while infectious entry was pH‐ and clathrin‐independent, it required multiple, endocytosis‐related factors and processes. The virions were found to undergo rapid internalization into large vacuoles containing internalized fluid and endosome markers. The characteristics of the internalization process fulfilled major criteria for macropinocytosis. Moreover, we found that soon after addition to fibroblasts the virus rapidly triggered the formation of circular dorsal ruffles in the host cell followed by the generation of large macropinocytic vacuoles. This distinctive form of macropinocytosis has been observed especially in primary cells but has not previously been reported in response to virus stimulation. Abstract : Human cytomegalovirus (HCMV) is a major contributor to disease in newborns and immunosuppressed patients. To date, treatment options are limited. Here we show that HCMV enters primary human fibroblasts by macropinocytosis. Because macropinocytosis is the HCMV entry route in endothelial, epithelial and dendritic cells, this entry mechanism is likely in most relevant cell types. In addition, we found that HCMV induces the formation of circular dorsal ruffles (CDRs). CDRs are commonly observed in primary cells during macropinocytosis but have not previously been observed after virus stimulation.